Aqueous Cation-Amide Binding: Free Energies and IR Spectral Signatures by Ab Initio Molecular Dynamics - Pluhařová, Eva; Baer, Marcel D; Mundy, Christopher J; Schmidt, Burkhard; Jungwirth, Pavel (The journal of physical chemistry letters, 2014)
Understanding specific ion effects on proteins remains a considerable challenge. N-methylacetamide serves as a useful proxy for the protein backbone that can be well characterized both experimentally and theoretically. The spectroscopic signatures in the amide I band reflecting the strength of the interaction of alkali cations and alkaline earth dications with the carbonyl group remain difficult to assign and controversial to interpret. Herein, we directly compute the infrared (IR) shifts corresponding to the binding of either sodium or calcium to aqueous N-methylacetamide using ab initio molecular dynamics simulations. We show that the two cations interact with aqueous N-methylacetamide with different affinities and in different geometries. Because sodium exhibits a weak interaction with the carbonyl group, the resulting amide I band is similar to an unperturbed carbonyl group undergoing aqueous solvation. In contrast, the stronger calcium binding results in a clear IR shift with respect to N-methylacetamide in pure water.
Keywords: N-methylacetamide; calcium; umbrella sampling; peptide bond; sodium